Encyclopedia of Electrochemistry 2002
DOI: 10.1002/9783527610426.bard090004
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry ofNAD(P)+/NAD(P)H

Abstract: The sections in this article are Introduction NAD ( P ) + / NAD ( P ) in Living Systems Formal Potential of the NAD + / NADH Redox Couple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 408 publications
0
54
0
Order By: Relevance
“…5,17,18 Electrode surface modification has been considered as a means of achieving an effective decrease in overpotential for NADH oxidation. 19,20 However, studies of unmodified electrodes are valuable both to provide a benchmark and to seek the optimal electrode format. The electrochemistry of NADH at conducting diamond has received attention, but the focus has mainly been on hydrogen-terminated diamond, 15,21 with oxygen terminated diamond 14 receiving only scant attention.…”
Section: Introductionmentioning
confidence: 99%
“…5,17,18 Electrode surface modification has been considered as a means of achieving an effective decrease in overpotential for NADH oxidation. 19,20 However, studies of unmodified electrodes are valuable both to provide a benchmark and to seek the optimal electrode format. The electrochemistry of NADH at conducting diamond has received attention, but the focus has mainly been on hydrogen-terminated diamond, 15,21 with oxygen terminated diamond 14 receiving only scant attention.…”
Section: Introductionmentioning
confidence: 99%
“…1 The efficient in situ regeneration of NADH from NAD + is valuable in biocatalysis due to the stoichiometric amount required for NADHdependent enzymes along with its relatively high cost. 1 It was reported that the combination of three NAD + -dependent dehydrogenases (formate dehydrogenase, formaldehyde dehydrogenase and alcohol dehydrogenase) is capable of generating methanol from CO 2 by reversing the original enzymatic reaction direction. [2][3][4][5] In this enzyme cascade, one molecule of methanol is produced at the cost of three equivalents of NADH.…”
mentioning
confidence: 99%
“…A convenient way to decrease the high overpotential and avoid fouling effect is to use suitable mediators that can facilitate the electron transfer kinetics. In this way, much effort has been made to identify/develop new materials that can effectively overcome the kinetic barriers for the electrochemical regeneration of NAD þ [35]. Nevertheless, such electrodes possess certain drawbacks, such as leaching of mediator and lack of long-term stability, which may limit their analytical application [36].…”
Section: Introductionmentioning
confidence: 99%